Preventing Fraud Through Internal Audit and Whistleblowing System - Ahmad Johan; Mirza Abdi Khairusy; Nugraha Nugraha; Sriwardini Sriwardini (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
This study aims to analyze the effect of Internal Audit and Whistleblowing System on Fraud Prevention at PT TASPEN (Persero) Bandung Main Branch Office. The factors tested in this study are internal audit and the violation reporting system as independent variables. Meanwhile, fraud prevention is the dependent variable. The research design used in this research is explanatory. The population in this study were 50 employees who were at PT TASPEN (Persero). The sampling technique used in this study is to use a saturated sample because the population size is known with certainty. While the analytical method used in this study is multiple linear regression analysis at a significance level of 5% using the Program (SPSS) Version 25. The results of hypothesis testing indicate that the internal audit and whistleblowing system have a significant effect on fraud prevention and contribute to fraud prevention by 66.4%. So that the better the level of internal audit and whistleblowing system in a company, the higher the level of fraud prevention.